2020
DOI: 10.1186/s40645-020-00391-7
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble flash flood predictions using a high-resolution nationwide distributed rainfall-runoff model: case study of the heavy rain event of July 2018 and Typhoon Hagibis in 2019

Abstract: The heavy rain event of July 2018 and Typhoon Hagibis in October 2019 caused severe flash flood disasters in numerous parts of western and eastern Japan. Flash floods need to be predicted over a wide range with long forecasting lead time for effective evacuation. The predictability of flash floods caused by the two extreme events is investigated by using a high-resolution (~ 150 m) nationwide distributed rainfall-runoff model forced by ensemble precipitation forecasts with 39 h lead time. Results of the determ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 51 publications
(42 reference statements)
0
11
0
1
Order By: Relevance
“…Flash flood modelling [CB-P, MY-P, TS-P] is also a key area that benefits from (and requires) high resolution models due to the ability to resolve convection and capture the variability in soil moisture (Loval et al, 2019;Hapuarachchi et al, 2011). Sayama et al [TS-P] showed that a 150 m resolution national rainfall-runoff model was able to predict two flash flood events reasonably well, although with large uncertainty in some locations due to the 5 km meteorological forecast being unable to confidently predict the location of the storm (Sayama et al, 2020). Sandu [IS-K] noted how high-resolution models made scaling effects and computational efficiency key considerations for current and future projects ([GS-P], Bauer et al, 2021;Donahue et al, 2020;Yepes-ArbĂłs et al, 2022).…”
Section: Physically-based Model Developmentmentioning
confidence: 99%
“…Flash flood modelling [CB-P, MY-P, TS-P] is also a key area that benefits from (and requires) high resolution models due to the ability to resolve convection and capture the variability in soil moisture (Loval et al, 2019;Hapuarachchi et al, 2011). Sayama et al [TS-P] showed that a 150 m resolution national rainfall-runoff model was able to predict two flash flood events reasonably well, although with large uncertainty in some locations due to the 5 km meteorological forecast being unable to confidently predict the location of the storm (Sayama et al, 2020). Sandu [IS-K] noted how high-resolution models made scaling effects and computational efficiency key considerations for current and future projects ([GS-P], Bauer et al, 2021;Donahue et al, 2020;Yepes-ArbĂłs et al, 2022).…”
Section: Physically-based Model Developmentmentioning
confidence: 99%
“…After an initial analysis of the performance of the three rainfall forecast products, the evaluation procedure proposed in this paper focused on the capacity of the hydrological forecasts to anticipate the exceedance of selected discharge thresholds. Several authors have suggested using thresholds and contingency tables to perform a robust regional evaluation of hydrological 535 ensemble forecasts (Silvestro and Rebora, 2012;Anderson et al, 2019;Sayama et al, 2020). In this study, a step further is proposed towards (i) focusing only on the rising limb phase of the flood hydrograph -i.e.…”
Section: Added Value and Limitations Of The Implemented Evaluation Fr...mentioning
confidence: 99%
“…The RRI is a two-dimensional model that has the advantage of simultaneously modeling runoff and flood inundation (Sayama et al 2012(Sayama et al , 2020P.C. et al 2020a, 2020bNguyen et al 2021).…”
Section: Hydrological Modelmentioning
confidence: 99%